Impact of TV Commercial, Social Media Advertising, and Point of Purchase on Brand Awareness Leading to Consumer Buying Intention on Brand “Cap Panda” - Henry Sugiarto Prasetyo; Hendra Achmadi (Budapest International Research and Critics University, 2022)
This study analyzes the relationship between TV commercial advertisements, social media, and the formation of a relationship with the point of purchase on Brand Awareness that influences the decision to buy the FMCG product